PEMBUATAN TELUR ASIN DENGAN MEDIA ABU GOSOK DAN BAWANG PUTIH - Raga Samudera; Siti Erlina; Gt. Khairun Ni’mah (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
The implementation of the devotion was carried out on a group of cattle island beautiful village banyan jaya kecamatan banjang kabupaten the upstream north .The purpose of devotion to provide information on various knowledge of tehnologi processing produce salted egg by the ashes rub and garlic .Done an explanation of the details turn tehnologi processing the results of products ranch such as materials and the procedure of making salted egg , through talk and question and answer on all pesetas and do practices making salted egg directly be noticed the group farmers .Activities devotion to these communities able to provide information and motivate to the participants to do business peningkatkan cattle and the increase income advantage which in turn will enhance kesejahtraan farmers